Malaysia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper highlights that growth in Malaysia accelerated in 1994-95, underpinned by strong domestic and external demand. Exports of goods and services accelerated in 1994, owing to strong overseas demand and expanded production capacity, particularly in the electronics and electrical products industries. Private fixed capital formation grew by more than 25 percent per year (in real terms), in response to lower corporate tax rates, an increase in the reinvestment allowance, the decline in interest rates during 1994 and early 1995, and strong demand.